A comprehensive theoretical model for the centrifugal effect of nonlinear beam-type piezoelectrical energy harvesters in rotational motions. (15th April 2023) - Mei, Xutao; Du, Houfan; Zhou, Shengxi
Highlights: A comprehensive theoretical model for beam-type PEHs with an installation angle is established. The proposed model can account for the centrifugal effect depending on the installation angle and rotational radius. Adjusting the installation angle is experimentally proved to be a promising way to change the effective frequency range. Abstract: Currently, beam-type piezoelectric energy harvesters (PEHs) are being widely studied to realize rotational energy harvesting with high-efficiency performance. However, few theoretical models completely reveal the mechanism of the centrifugal effect, which results from the centrifugal force acting on the tip mass of beam-type PEHs. To fill in this research gap, a theoretical model has been established to describe its dynamic behaviors in this paper, and also account for the impacts of the installation angle and the rotational radius on the centrifugal effect. According to the proposed theoretical model, influences of the centrifugal force on dynamic characteristics and power generations are explored. Theoretical results demonstrate that the installation angle has a significant influence on components of the centrifugal force. Namely, the axial component can stiffen or soften the piezoelectric beam and the transverse component can be regarded as an excitation force, influencing the dynamic behaviors of beam-type PEHs. In addition, experiments of an asymmetric beam-type PEH with different installation angles are performed to validate the effect of the centrifugal effect and the magnetic force on its performance. Experimental results demonstrate that adjusting the installation angle to realize different centrifugal effects can change the effective frequency range and also be beneficial for power generation. Additionally, the asymmetric tri-stability due to the magnetic force can reduce the potential barrier to increase the effective frequency bandwidth. Overall, this paper reveals the mechanism of the centrifugal effect, and further provides theoretical insights into high-efficiency design and optimizations for beam-type PEHs in rotational motions.